Hydrogels With Integrin-Binding Angiopoietin-1–Derived Peptide, QHREDGS, for Treatment of Acute Myocardial Infarction. (March 2015) - Reis, Lewis A.; Chiu, Loraine L.Y.; Wu, Jun; Feric, Nicole; Laschinger, Carol; Momen, Abdul; Li, Ren-Ke; Radisic, Milica
Abstract : Background—: Hydrogels are being actively investigated for direct delivery of cells or bioactive molecules to the heart after myocardial infarction (MI) to prevent cardiac functional loss. We postulate that immobilization of the prosurvival angiopoietin-1–derived peptide, QHREDGS, to a chitosan-collagen hydrogel could produce a clinically translatable thermoresponsive hydrogel to attenuate post-MI cardiac remodeling. Methods and Results—: In a rat MI model, QHREDGS-conjugated hydrogel (QHG213H), control gel, or PBS was injected into the peri-infarct/MI zone. By in vivo tracking and chitosan staining, the hydrogel was demonstrated to remain in situ for 2 weeks and was cleared in ≈3 weeks. By echocardiography and pressure–volume analysis, the QHG213H hydrogel significantly improved cardiac function compared with the controls. Scar thickness and scar area fraction were also significantly improved with QHG213H gel injection compared with the controls. There were significantly more cardiomyocytes, determined by cardiac troponin-T staining, in the MI zone of the QHG213H hydrogel group; and hydrogel injection did not induce a significant inflammatory response as assessed by polymerase chain reaction and an inflammatory cytokine assay. The interaction of cardiomyocytes and cardiac fibroblasts with QHREDGS was found to be mediated by β1 -integrins. Conclusions—: We demonstrated for the first time that the QHG213H peptide–modified hydrogel can be injected in the beating heart where it remains localized for a clinically effective period. Moreover, the QHG213H hydrogel induced significant cardiac functional and morphological improvements after MI relative to the controls. Abstract : Supplemental Digital Content is available in the text.